PERAN KELURAHAN SIAGA BENCANA GUNA PENANGGULANGAN BENCANA BANJIR DI KELURAHAN MUKTIHARJO LOR KECAMATAN GENUK KOTA SEMARANG - Irawan, David; Subowo, Ari (Journal of Public Policy and Management Review, 2016)
Natural disasters are natural events that harm or threaten in human life. The potential occurrence of a disaster is always there all of the time and disasters can happened anytime and therefore needed handling with disaster preparedness. In responding to disasters Semarang make Semarang Regional Regulation No. 13 of 2010 on Disaster Management. Through the Regional Disaster Management Agency (BPBD) government involving the community by creating a Village Disaster Alert (KSB). The purpose of this study was to determine the role of KSB Muktiharjo Lor districtsof Genuk in response to floods in the Muktharjo Lor District of Genuk. This research uses descriptive qualitative approach. Data collection techniques used were observation, interviews, documentary studies and literature. Results from this study is the difference in point views of KSB with BPBD. The government saw that the establishment of the KSB to the public as subordinate of government in handling disaster and its members are volunteers. But KSB members found it hard to to be a volunteer and hopes to become members of KSB wages. Need better coordination in order in handling disasters can be more responsive.